Trajetórias familiares e práticas de gestão : estudo de caso da família Gottardo em Guarapari - Machado, Marcelo Tedoldi (2005)
Inserted in a subjective perspective of research on family companies, this work search to add to the effort for interpretation of partner-cultural dynamics, opposing to the that just treat referring subjects about the succession. The research has qualitat